The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.14202/vetworld.2017.1205-1211
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction detection of genes responsible for multiple antibiotic resistance Staphylococcus aureus isolated from food of animal origin in Egypt

Abstract: Aim:The aim of our study was polymerase chain reaction (PCR) detection of the genes responsible for the multiple antibiotic resistance S. aureus isolated from food of animal origin in Egypt.Materials and Methods:A total of 125 samples were randomly collected from milk, meat, and their products from Giza and Beni-Suef Governorates markets. The S. aureus isolates were subjected to antimicrobial sensitivity tests using four antibacterial disks (Oxoid), and then the polymerase chain reaction (PCR) was performed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
7
12
1
Order By: Relevance
“…For dairy product studies, in Algeria, similar results were reported, as described by [20,43,44]. In contrast, the prevalence obtained was higher than that found in Egypt (12%) [45], (16.60%) [23], Nigeria (9.15%) [46], China (1.8%) [22], Greece (18%) [27], Spain (7%) [26], and Italy (9.79%) [47] (11.77%) [29], with the highest prevalence registered in Georgia [12] and Turkey [48] with (63%) and (42.50%), respectively.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For dairy product studies, in Algeria, similar results were reported, as described by [20,43,44]. In contrast, the prevalence obtained was higher than that found in Egypt (12%) [45], (16.60%) [23], Nigeria (9.15%) [46], China (1.8%) [22], Greece (18%) [27], Spain (7%) [26], and Italy (9.79%) [47] (11.77%) [29], with the highest prevalence registered in Georgia [12] and Turkey [48] with (63%) and (42.50%), respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Our antimicrobial analysis showed that the highest resistance among all antibiotics tested was against tetracycline (58%), followed by oxacillin (36%), fosfomycin (33%), penicillin (25%), and erythromycin (23%). The resistance to tetracycline remains the most common, with a high prevalence, which is in concord with several earlier reports from sausage [14] and different meat products [16,22,23,25,43,55,56]. In contrast, Aydin et al .…”
Section: Discussionsupporting
confidence: 58%
“…Investigations of the antibacterial activity of β-lactams on susceptible bacterial strains using biochemical techniques ( Kumarasamy et al, 2010 , El Seedy et al, 2017 ), scanning electron microscope (SEM), ( Hartmann et al, 2010 , Napiroon et al, 2017 ), and transmission electron microscope (TEM) ( Hartmann et al, 2010 , Bæk et al, 2014 , Napiroon et al, 2017 ) is well documented in the literature. For example, biochemical techniques such as polymerase chain reaction (PCR) could assess specific resistance genes that may be expressed in antibiotic-resistant bacteria upon exposure to antibiotics ( Fluit et al, 2001 , Kumarasamy et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, biochemical techniques such as polymerase chain reaction (PCR) could assess specific resistance genes that may be expressed in antibiotic-resistant bacteria upon exposure to antibiotics ( Fluit et al, 2001 , Kumarasamy et al, 2010 ). The use of PCR has confirmed many potential antibiotic-resistant genes and their concomitant mechanisms ( Kumarasamy et al, 2010 , Ali et al, 2014 , El Seedy et al, 2017 ). Despite the huge potentials, genetic methods provide in exploring antibiotic resistance, there have few limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the popularity of RTE meats in Nigeria, the meats may be prone to microbial contamination due to some predisposing factors. High protein and water contents of the meats make them very susceptible to microbial contamination and multiplication [ 9 ], especially in the Tropics where climatic conditions favor the persistence and proliferation of most microbial pathogens [ 4 - 7 ]. The presence of microbial contaminants, especially Staphylococcus species, in RTE meats has generated a lot of public health and food safety concerns globally [ 10 , 11 ], due to their enormous pathogenic and zoonotic potentials [ 12 ] and the ease of transmission of the organisms to humans through consumption of the contaminated meat [ 13 ].…”
Section: Introductionmentioning
confidence: 99%